Screening of elite black soybean lines for resistance to rust disease, Phakopsora pachyrhizi - AYDA KRISNAWATI; GATUT WAHYU A. S.; M. MUCHLISH ADE (Society for Indonesian Biodiversity, 2016)
risnawati A, Gatut-Wahyu AS, Adie MM. 2016. Screening of elite black soybean lines for resistance to rust disease, Phakopsora pachyrhizi. Biodiversitas 17: 134-139. Indonesian tropical climate is ideal for both of soybean growth and harmful disease development. Soybean rust, Phakopsora pachyrhizi, has been a serious disease in Indonesia and may have an impact on soybean production. The objective of the study was to evaluate the resistance of elite black soybean lines to rust disease. Agronomic characters (yield and yield component) were evaluated based on research conducted in 16 soybean production centers in Indonesia. The evaluation for rust resistance was conducted in Indonesian Legumes and Tuber Crops Research Institutes' greenhouse in 2011 using ten elite black soybean lines. The seed yield of ten black soybean lines grown in 16 locations ranged from 2.51-2.88 t/ha, with an average of 2.59 t/ha. The eight lines showed higher yield than check cultivar of Malika, whereas only one line (W9837 × Cikuray-66) had higher yield than check cultivar of Detam-1. Resistance reaction to rust disease fluctuates over time. Two elite lines of Cikuray × W9837-171 and Cikuray × W9837-184 showed a consistent resistance to P. pachyrhizi. W9837 × Cikuray-66 and check cultivar of Detam-1 consistently showed a moderately resistant. In the terms of agronomic aspects, W9837 × Cikuray-66, which has moderately resistant to P. pachyrhizi, produced the highest yield (2.88 t/ha). The both of resistant lines of Cikuray × W9837-171 and Cikuray × W9837-184 have early maturity, and medium seed size with yield 2.57 t/ha and 2.56 t/ha, respectively. The resistant and moderate lines with high yield, early maturing, and medium seed size found in this study playing an important role in the soybean varietal development program for rust resistance in Indonesia.